How to improve primary school students’ social participation in the inclusive classroom? – Preliminary results from an intervention study. Oral Communication. Symposium “FRIEND-SHIP: A school-based intervention aimed at improving students’ social participation implemented in four countries” (Sílvia Alves). Porto International Conference on Research in Education 2022 (ICRE 2022) - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

The relationship between primary school students’ contact experiences and their attitudes towards peers with non-compliant behaviour. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Teachers’ intentions to deal with heterogeneity in inclusive and non-inclusive primary schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Characteristics of good inclusive teaching from primary school teachers’ perspective. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Görel, Gamze; Franzen, Katja; Hellmich, Frank

Teachers’ experiences from teaching in (non-)inclusive primary schools and their behavioural intentions to manage heterogeneity. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022) - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Primary school teachers’ mastery experiences and their self-efficacy beliefs to teach in inclusive classrooms. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022) - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Two-Sided Endless Optical Polarization Control with 2 x 100 krad/s Tracking Speed - Noé, Reinhold; Koch, Benjamin (Photonic Networks; 23th ITG-Symposium)

Global weak solutions to a chemotaxis-Navier-Stokes system in $R^3$. - Kang, Kyungkeun; Lee, Jihoon; Winkler, Michael (Discrete and Continuous Dynamical Systems)

Eine meta-analytische Untersuchung der Feedback-Related Negativity in motorischen Aufgaben - Faßbender, Laura; Krause, Daniel; Weigelt, Matthias

Sport Emotion Questionnaire (SEQ) – Nur ein Messinstrument zur Er-fassung wettkampfbezogener Emotionen oder kann der SEQ auch im Freizeit- und Gesundheitssport zum Einsatz kommen? - Thorenz, Kristin; Weigelt, Matthias

Mental rotation of tactic board instructions in basketball: Domain-specific expertise improves on-court performance - Krause, Daniel; Weigelt, Matthias

The affective response to moderate physical activity and relaxation exercises - Thorenz, Kristin; Sudeck, Gorden; Weigelt, Matthias

Ästhetik und Funktion des Passionsspiels - Egidi, Margreth (Beiträge zur Geschichte der deutschen Sprache und Literatur)
Abstract The article combines an analysis of the ›Egerer Passionsspiel‹ with the fundamental question of the aesthetics, textual economy and function of late medieval Passion plays; it includes references to other genres and media of the Passion. According to the thesis, the Passion plays are characterised by the contradictory structure of two opposing representational concepts which are to be distinguished: the textual staging of violence and the representation of suffering. Both, as well as the becoming of Jesus as object resp. subject, are closely linked as textual processes with the bringing forth of the body of Jesus in the text. In contrast to other genres and media of the Passion, Passion plays potentially aim at a ›de-automation‹ of the transformation of violent events in the sense of suffering that was automated in medieval Passion culture.
Keywords: Geistliches Spiel; Passionsspiel; Passionsfrömmigkeit; Textperformativität

Sonderpädagogische Diagnostik im Spannungsfeld von Kategorisierung, Dekategorisierung und Rekategorisierung - Lütje-Klose, Birgit; Neumann, Phillip (Sonderpädagogik - zwischen Dekategorisierung und Rekategorisierung)
Keywords: Inklusion; Diagnostik; Sonderpädagogik; Inklusive Pädagogik; Förderplanung; Bildungsstatistik; Schulentwicklung

Care! Zum Verhältnis von Sorge und Sozialer Arbeit – eine Einleitung - Bomert, Christiane; Landhäußer, Sandra; Lohner, Eva Maria; Stauber, Barbara (Care! Zum Verhältnis von Sorge und Sozialer Arbeit)
Die während der Corona-Pandemie sehr deutlich gewordenen prekären Bedingungen für Sorgearbeit in Familien, Kindergärten, Schulen und Altersheimen verweisen auf komplexe, strukturelle und andauernde Ungleichheiten. Da die Soziale Arbeit selbst in verschiedenen Care-Kontexten agiert, ist ihre kritische Auseinandersetzung mit Care unerlässlich. Diese anzuregen ist Ziel des Bandes. Dazu werden Delegations-, Feminisierungs-, Entwertungs- und Prekarisierungsprozesse von Care aufgezeigt und Verbindungen von Sorge und Sozialer Arbeit skizziert, die in den Beiträgen des Bandes aufgegriffen werden.
Keywords: Fürsorge Feminismus Vulnerabilität Prekäre Professionalität Altenhilfe Kindertageseinrichtungen Familie Gemeinwesenarbeit Care-Revolution Ökonomisierung

Care im Kontext von Gemeinwesenarbeit und Sozialraumorientierung. Ein Dialog mit Sandra Landhäußer und Maren Schreier - Landhäußer, Sandra; Schreier, Maren; Lohner, Eva Maria; Bomert, Christiane (Care! Zum Verhältnis von Sorge und Sozialer Arbeit)
Der Band hat zum Ziel verschiedene Dimensionen von Care ins Verhältnis zur Sozialen Arbeit zu setzen und diese wechselseitigen Verknüpfungen kritisch zu beleuchten. Die Relevanz einer solchen Verhältnisbestimmung ergibt sich aus der Beobachtung, dass Care im Kontext der Sozialen Arbeit bislang kaum explizit behandelt wird. Es werden grundsätzliche Konfliktlinien beleuchtet, Einblicke in exemplarische Felder gegeben sowie bereits existierende Alternativen, Möglichkeiten für Solidarisierung und soziale Innovationen aufgezeigt.
Keywords: Sozialwissenschaften; Pädagogik; Sozialpädagogik Sozialwissenschaften; Politik / Verwaltung; Altenhilfe • Care-Revolution • Familie • Feminismus • Führsorge • Fürsorge • Gemeinwesenarbeit • Gemeinwesenarveit • Kindertageseinrichtungen • Ökonomisierung • Prekäre Professionalität • Vulnerabilität

Review on: Gerold Ambrosius/ Christian Henrich-Franke: Diversität, Transformation, Kontinuität. Europa 1800–1870 - Schönhärl, Korinna (VSGW)

An Open-Source Transistor Database and Toolbox as a Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (2022 IEEE Applied Power Electronics Conference and Exposition (APEC))

An Open-Source FEM Magnetics Toolbox for Power Electronic Magnetic Components - Förster, Nikolas; Piepenbrock, Till; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (PCIM Europe 2022; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730). Einleitung. - Steigerwald, Jörn (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))